Increasing Learning Results Of Bolavoly Low Passing Using Hanging Ball Media In Class IV Students Of Waikoro State Elementary School - veramita Maria Marta; Ronald Dwi Ardian Fufu; Ramadhan Kasim (Universitas Nusa Cendana, 2021)
This research is motivated by the use of instructional media that is not in accordance with the characteristics of students which causes students to be uninterested and less active during the learning process so that student learning outcomes decline. This study aims to determine the improvement of the process of learning under passing by using a hanging ball media on the fourthgrade students of the SD Negeri Waikoro. This research is a Classroom Action Research (CAR) which consists of two cycles, in each cycle there are four stages, namely planning, implementation, observation and reflection. The subjects of this study were 15 class IV students of Waikoro Public Elementary School consisting of 15 students consisting of 11 male students and 4 female students. The physical condition of students is physically and mentally healthy. The results showed that by using hanging ball media can improve the results of learning under passing in class IV SD Negeri Waikoro, in cycle I and cycle II, the results of learning to pass under the first cycle, the average value obtained was 70.55 with completeness classical 33.33%. In cycle II the average value of students increased to 81.11 with classical completeness reaching 93.33%